Knowledge, Attitude and Practices of Diabetic Patients about Skin Care (Ibrahim Cardiac Medical Journal, 2012)
Background: Diabetes is now a public health problem in our country and it is steadily increasing. Skin manifestation is frequently common in diabetics. Care of skin is a part of management, where patient's role is no less than a physician, The patients' role includes perception and practice of the patients about their skin manifestation. This cross-sectional study was, therefore, undertaken to assess the knowledge, attitude and practice of diabetic patients (respondents) about their skin care.Methods: The study was carried out in the Department of Dermatology, National Healthcare Network, Dhaka over a period of 6 months from April to September 2009. A total of 90 diabetic patients with or without skin diseases included in the study. The level of knowledge and practice was measured on a 0-4 Likert Scale.Results: Respondents were predominantly male (60%) with mean age being 49±11.1 years.  Majority (95%) of the respondents were Muslim (95%), educated (87.7%) and middle class (83.3%). Primary and secondary level educated comprised 50% of the respondents. Over 25% was graduate and higher level educated and the rest (13.3%) illiterate. About 88% of the respondents held the view that diabetic patients were more susceptible to develop skin diseases and over 75% were aware about skin manifestations in diabetics. Although majority (98.1%) had a good knowledge about what to do in case if skin manifestation arises, less than half (45%) had knowledge about how to take care of their skin (unaware about practice). Only 36% of the respondents told that changes in skin colour should often be checked as evidence of skin manifestation (good knowledge), 31.1% told sometimes to be checked (fair knowledge) and 33.3% told never to be checked (poor knowledge). Majority of the respondents categorized pruritis (85.6%), erythema (81.1%) and impetigo (80%) as skin diseases. Pigment disorder, epidermal differentiation disorder, papules and blisters were identified by around two-thirds of the diabetics. Changes in skin pigmentation, cuts and blisters were often checked by 30% of the diabetics. Changes in red spots, swelling and sensation were often checked by 10% of the respondents. Nearly three-quarters (22%) of the respondents' knowledge about skin care was highly satisfactory in terms of Likert scale, followed by 44.4% satisfactory, 17.8%  more or less satisfactory, 10% grossly dissatisfactory and 5.6% poor.Conclusion: The study concluded that diabetic patients are aware of their skin manifestation and its different forms. They also possess good knowledge about how to take care of those manifestations. But they are usually reluctant to bring it into practice.Ibrahim Cardiac Med J 2012; 2(2): 31-36